Comparison of chromosome banding analysis, interphase- and hypermetaphase-FISH, qualitative and quantitative PCR for diagnosis and for follow-up in chronic myeloid leukemia: a study on 350 cases - Haferlach, Claudia; Schnittger, S.; Bursch, S.; Gerstner, D.; Hochhaus, Andreas; Berger, Ute; Hehlmann, Rüdiger; Hiddemann, W.; Haferlach, T. (Leukemia, 2002)
For the diagnosis of CML and for monitoring of treatment response the detection of the t(9;22)(q34;q11) or the BCR-ABL rearrangement is necessary. Chromosome banding analysis (CA) is still the gold standard but other techniques like Southern blot, fluorescence in situ hybridization (FISH) and polymerase chain reaction (PCR) are available. We analyzed 350 CML patients at different stages of disease in parallel with CA, interphase-FISH (IP-FISH), hypermetaphase-FISH (HM-FISH) and RT-PCR. In 20 cases with no Ph+ metaphases in CA, HM-FISH detected 0.2 to 10% BCR-ABL+metaphases. After IP-FISH 107 samples were judged as negative. However, in 17 of these samples HM-FISH detected BCR-ABL+ metaphases (0.3-11%), and in eight cases CA detected Ph+ metaphases (2.5-25%). A comparison of IP-FISH performed on uncultivated cells vs cells cultivated for 48 h in 70 cases revealed a higher proportion of BCR-ABL+ cells in the cultivated samples. If nested PCR was negative, all other methods were negative in all cases too. In addition, 94 cases were evaluated using real-time PCR (LightCycler technology). The BCR-ABL/cABL ratio measured showed a high correlation with all other methods. Interestingly, a wide range in the BCR-ABL/ABL ratio was observed especially in patients who showed 100% Ph-positive metaphases in CA. In conclusion, CA, IP-FISH, HM-FISH and real-time PCR give reliable results but differences due to measurement of different target structures have to be kept in mind when using these data for definition of remission status.
Gesehen am 16.05.2022